Edukasi Obat pada Masyarakat Bebasis Ibu Rumah Tangga Menggunakan Model Permainan Pintar dengan Obat (Piano) - Syofyan Syofyan; Dachriyanus Dachriyanus; Masrul Masrul; Rosfita Rasyid; Erizal Erizal; Hadi Ihsan; Agung Tri Sasongko (Warta Pengabdian Andalas, 2019)
Many people's behavior in using medicines is still incorrect. The intended behavior is starting from how to get, use, store and dispose of drugs. This is inseparable from the factor of low knowledge about medicines. Community service activities aim to provide appropriate education to the community related to the above drug problems. As partners are the PKK Team of Talago Sariak Village, Pariaman City is a housewife. Selection of housewives as targets because housewives are usually the most responsible community groups in terms of managing medicines in the household or family. The activity method is in the form of using a game model that is Smart with medicines (PIANO) and questionnaires in the form of pre-test and post-test. The results showed that there was an increase in people's knowledge and attitudes about medicine, where the percentage of the average score of knowledge increased from 50.6% to 69.4%. Likewise with attitudes from 67.36% to 73.46%. From these results, it can be concluded that education about medicines using the PIANO game model can be a pretty good educational model in helping to improve people's knowledge and attitudes about medicine.